Transition process to experience with elimination intestinal stoma: repercussions on body image (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: to know the process of transition and adaptation to the experience with elimination intestinal stoma. Methods: a descriptive-exploratory, mixed study conducted between May and July 2018 through a semi-structured interview and application of the body image scale with 13 people with a stoma, at the postoperative return in a federal hospital in the south of the country. The data analysis was by thematic categories and simple descriptive analysis. Results: The data showed a parity between the genders, mean age of 60.5 years, most parts married, with low education level, and away from work activities. The leading generator causes of stoma were neoplasias, stomas with more than six months, and temporary. The most frequently identified complications were intestinal loop prolapse and dermatitis. The most significant changes occurred in the food pattern, clothing, social behavior, and body image reflexes. The premorbid body subscale had an average of 22.23 points, and the subscale morbid body had an average of 15.15 points. Conclusion: The condition of being a person with a stoma has an impact on the way the individual sees their body. It is essential to highlight that individuals at risk of maladaptation are identified and addressed as early as possible.
Keywords: Stoma; Body image; Nursing; Stomatherapy